Axon guidance in Drosophila - Thomas, John (Henry Stewart Talks, 2008)
How axons grow, The growth cone, The Drosophila nervous system, Receptors and ligands involved in axon guidance events, Attractive and repulsive receptor signaling, Integration of receptor signals in the growth cone, Conservation of axon guidance mechanisms during evolution
Reviewed at 2023/06/19